Provisions of Air Carrier Liability in Libyan Law and International Treaties (Al-Mukhtar Journal of Legal Science, 2025)
When regulating air transport regulations, national legislation and international agreements have sought to outline the legal provisions governing the air carrier's liability for accidents. This is done with the aim of providing fair protection for the victims of such accidents and ensuring their right to compensation commensurate with the extent of the damages they incur. This study addresses the legal regulation of air carrier liability in both domestic and international transport. It outlines its legal basis and scope, as one of the most important issues raised regarding air carrier liability. This study, in light of the issues, identifies the circumstances in which the carrier may be exempted from liability. It also demonstrates the extent to which the legislator has been able to strike a balance between the interests of carriers on the one hand and those affected by the incident on the other.
Keywords: Air Transport; Contractual Liability; Accidents; Fault; Damage